Antibacterial and Osteogenic Functionalization of Titanium With Silicon/Copper-Doped High-Energy Shot Peening-Assisted Micro-Arc Oxidation Technique - Shen, Xinkun; Hu, Wenjia; Ping, Linchao; Liu, Chongxing; Yao, Lili; Deng, Zhennan; Wu, Gang (Frontiers in Bioengineering and Biotechnology, 2020)
Antibacterial and osteogenic functionalization of titanium (Ti) implants will greatly expand their clinical indications in immediate implant therapy, accelerate osteointegration and enhance long-term prognosis. We had recently shown that the high-energy shot peening (HESP)-assisted micro-arc oxidation (MAO) significantly improved the bioactivity and coating stability of Ti-based substrates. In this study, we further functionalized Ti with antibacterial and osteogenic properties by doping silicon (Si) and/or copper (Cu) ions into HESP/MAO-treated coatings. Physicochemical characterization displayed that the doping of Si and Cu in HESP/MAO-treated coatings (Si/Cu-MAO) did not significantly change their surface topography, roughness, crystal structure, coating thickness, bonding strength, and wettability. The results of X-ray photoelectron spectroscopy (XPS) showed that Si and Cu in the Si/Cu-MAO coating was in the form of silicate radical (SiO32-) and bivalent copper (Cu2+), respectively. The total amounts of Si and Cu were about 13.5 and 5.8 μg/cm2, which released about 33.2% and 31.3% within 14 d, respectively. Compared with the control group (MAO), Si doping samples (MAO-Si) significantly increased the cell viability, alkaline phosphatase (ALP) activity, mineralization and osteogenic genes (ALP, collagen I and osteocalcin) expression of MC3T3-E1 cells. Furthermore, the addition of Cu presented good bactericidal property against both Staphylococcus aureus and Streptococcus mutans (even under the co-culture condition of bacteria and MC3T3-E1 cells): the bacteriostatic rate of both bacteria was over 95%. In conclusion, the novel bioactive Si/Cu-MAO coating with antibacterial and osteogenic properties is a promising functionalization method for orthopedic and dental implants, especially in the immediate implant treatment with an infected socket.